Effects of perfume on mechanical and color properties of cotton fabrics. Issue 1 (2nd March 2015) - Kayar, Mahmut
Abstract : Purpose: – The purpose of this paper is to examine the effects of perfume on cotton fabrics and satisfy the perfume user's curiosity on this issue. Design/methodology/approach: – In this study, the selected perfume was applied on woven and knitted cotton fabric samples in order to investigate the effects of perfume on mechanical and colour properties of the fabrics. For this purpose the chosen perfume was applied in two different amounts (four spraying and eight spraying) from the same distance to the fabric surface. Then the fabric samples were left for 24 hours in order to fulfill the daily usage conditions. Samples were evaluated in terms of tensile strength, pilling and abrasion tests, respectively. Colour measurement test was performed for investigating the fading effect of the perfume and FTIR analysis was carried out for examining the chemical changes. Findings: – Result of the study revealed that perfume did not have any effects on tensile strength properties of cotton knitted and woven fabrics and caused serious decrease in pilling and abrasion values and negatively affected colour characteristics of fabrics. Originality/value: – In literature there was no study investigating the effect of perfume on mechanical and colour properties of garment. Thus this study will be the first concerning this issue.